Sulfonated Microporous Polymer Membranes with Fast and Selective Ion Transport for Electrochemical Energy Conversion and Storage. (31st March 2020) - Zuo, Peipei; Li, Yuanyuan; Wang, Anqi; Tan, Rui; Liu, Yahua; Liang, Xian; Sheng, Fangmeng; Tang, Gonggen; Ge, Liang; Wu, Liang; Song, Qilei; McKeown, Neil B.; et al.
Abstract: Membranes which allow fast and selective transport of protons and cations are required for a wide range of electrochemical energy conversion and storage devices, such as proton‐exchange membrane (PEM) fuel cells (PEMFCs) and redox flow batteries (RFBs). Herein we report a new approach to designing solution‐processable ion‐selective polymer membranes with both intrinsic microporosity and ion‐conductive functionality. Polymers are synthesized with rigid and contorted backbones, which incorporate hydrophobic fluorinated and hydrophilic sulfonic acid functional groups, to produce membranes with negatively charged subnanometer‐sized confined ionic channels. The ready transport of protons and cations through these membranes, and the high selectivity towards nanometer‐sized redox‐active molecules, enable efficient and stable operation of an aqueous alkaline quinone redox flow battery and a hydrogen PEM fuel cell. Abstract : Membranes : Sulfonated polyxanthene membranes with both intrinsic microporosity and conductive functionality were synthesized. They exhibit high ion conductivity and high selectivity towards redox‐active anions. They significantly enhance the performance of redox flow batteries and hydrogen fuel cells, demonstrating the design is broadly applicable.